Bicuspid Aortic Valve Disease: Classifications, Treatments, and Emerging Transcatheter Paradigms - Ankur Kalra, MD; Rajiv Das, MB ChB, MD; Mohammad Alkhalil, MD, DPhil; Iryna Dykun, MD; Alessandro Candreva, MD; Omar Jarral, MBBS, PhD; Syed M. Rehman, MBBS; Monil Majmundar, MD; Kunal N. Patel, MD, MPH; Josep Rodes-Cabau, MD, PhD; Michael J. Reardon, MD; Rishi Puri, MBBS, PhD (Structural Heart, 2024)
Bicuspid aortic valve (BAV) is a common congenital valvular malformation, which may lead to early aortic valve disease and bicuspid-associated aortopathy. A novel BAV classification system was recently proposed to coincide with transcatheter aortic valve replacement being increasingly considered in younger patients with symptomatic BAV, with good clinical results, yet without randomized trial evidence. Procedural technique, along with clinical outcomes, have considerably improved in BAV patients compared with tricuspid aortic stenosis patients undergoing transcatheter aortic valve replacement. The present review summarizes the novel BAV classification systems and examines contemporary surgical and transcatheter approaches.